2014
DOI: 10.1124/mol.114.091728
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Induces Redox-Based Changes in Global DNA Methylation and Retrotransposon Transcription by Inhibition of Excitatory Amino Acid Transporter Type 3–Mediated Cysteine Uptake

Abstract: Canonically, opioids influence cells by binding to a G proteincoupled opioid receptor, initiating intracellular signaling cascades, such as protein kinase, phosphatidylinositol 3-kinase, and extracellular receptor kinase pathways. This results in several downstream effects, including decreased levels of the reduced form of glutathione (GSH) and elevated oxidative stress, as well as epigenetic changes, especially in retrotransposons and heterochromatin, although the mechanism and consequences of these actions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
86
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 55 publications
7
86
0
Order By: Relevance
“…While the mechanism underlying inhibition of cysteine uptake by food-derived opiate peptides is not fully established, we previously found that protein kinase A (PKA) and/or Mitogen activated protein kinase kinase (MEKK) might be involved in mediating the effects of morphine on EAAT3 (50). The inhibitory effects on cysteine uptake are also observed at the levels of redox status and methylation capacity as well as at the DNA methylation status and the transcription levels of genes involved in maintaining the redox methylation homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…While the mechanism underlying inhibition of cysteine uptake by food-derived opiate peptides is not fully established, we previously found that protein kinase A (PKA) and/or Mitogen activated protein kinase kinase (MEKK) might be involved in mediating the effects of morphine on EAAT3 (50). The inhibitory effects on cysteine uptake are also observed at the levels of redox status and methylation capacity as well as at the DNA methylation status and the transcription levels of genes involved in maintaining the redox methylation homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to methylation and acetylation modifications of histones, morphine exposure induces methylation changes on DNA directly (Nielsen et al, 2008; Chorbov et al, 2011; Doehring et al, 2013; Trivedi et al, 2014). Morphine modulates cellular oxidative stress and methyl group donation through the antioxidant glutathione and the methyl donor SAM, respectively (Trivedi et al, 2014).…”
Section: Inheritance Of Drug Exposurementioning
confidence: 99%
“…Morphine modulates cellular oxidative stress and methyl group donation through the antioxidant glutathione and the methyl donor SAM, respectively (Trivedi et al, 2014). Consequently, as the redox state of the cell impacts methylation events, DNA methylation changes can occur following morphine exposure.…”
Section: Inheritance Of Drug Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that increasing the concentration of L1 RNA increased its inhibitory effect on PSF/DNA binding affinity. L1 RNA is transcribed from endogenous genomic retrotransposons and the level varies depending on the cell type and the level of global hypomethylation (25). Thus, the key parameters that determine whether GAGE6 expression is repressed by PSF or induced by L1 RNA are the type of cell and the global hypomethylation status.…”
Section: Discussionmentioning
confidence: 99%